Positive electrode material, preparation method thereof and sodium-selenium battery
By using accordion-like MXene material and transition metal nanoparticles modified positive electrode material in sodium selenium batteries, loading Se particles, the cycle stability problem of sodium selenium batteries is solved, and high power density, high energy density and long-term circulation capabilities are achieved.
Patent Information
- Application Number
- CN202510136152.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Sodium-selenium batteries face huge challenges in cycling stability, mainly due to the volume expansion effect of selenium, the shuttle effect of polyselenide, and the low reactivity between sodium and selenium electrodes.
A positive electrode material including host material and Se particles is used. The host material consists of accordion-shaped MXene material and transition metal nanoparticles. Se particles are supported between the surface of the MXene material and its layered structure. This structure promotes the reaction kinetics between the sodium electrode and the selenium electrode by limiting the volume expansion of selenium, inhibiting the shuttle effect of polyselenide, and promoting the reaction kinetics between the sodium electrode and the selenium electrode through transition metal nanoparticles.
The high power density and energy density of sodium selenium batteries are achieved, and the excellent long-term circulation capability is shown, which can maintain high specific capacity and stable electrochemical performance at high charging rates.
Smart Images

Figure CN119742358A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technologies, specifically to a cathode material, its preparation method, and a sodium-selenium battery. Background Art
[0002] In a sodium-selenium (Na-Se) battery, the selenium electrode has a high theoretical specific capacity, a high theoretical volumetric specific capacity, a high electronic conductivity, and the selenium electrode combines with an ether-based electrolyte. By promoting the dissolution of reaction intermediates in the Na-Se battery, the solid-phase diffusion is effectively converted into liquid-phase diffusion, enabling the sodium-selenium battery to have a high energy density and a high power density. However, selenium-based energy storage still faces great challenges in achieving cycle stability, which is attributed to the significant swelling effect and the shuttle effect of the intermediate Na2Se n (2 < n ≤ 8). In addition, the low reactivity between the sodium electrode and the selenium electrode is also a major influencing factor.
[0003] Currently, the commonly used solutions are mostly to react selenium with other substances to form compounds, thereby restricting the shuttle effect of polyselenides. Although these methods alleviate the problem of insufficient cycle life of sodium-selenium batteries to a certain extent, they are not beneficial to the low reactivity and slow reaction rate between the sodium electrode and the selenium electrode. Summary of the Invention
[0004] In view of this, the present invention provides a cathode material, its preparation method, and a sodium-selenium battery. This cathode material can achieve a high power density and a high energy density of the sodium-selenium battery and exhibit excellent long-term cycling ability.
[0005] To achieve the above-mentioned invention objectives, the present invention provides the following technical solutions: In a first aspect, the present invention provides a cathode material, which includes a host material and Se particles; The host material includes a MXene material and transition metal nanoparticles. The MXene material has an accordion-like layered structure, and the transition metal nanoparticles are modified on the surface of the MXene material; The Se particles are loaded on the surface of the MXene material and between its layered structures.
[0006] In an embodiment of the present invention, the chemical formula of the MXene material is M n+1 X n T x , where M is at least one of transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, Hf, X is C and / or N element, T x is at least one of surface functional groups -O, -Cl, -OH, -F, and n is the number of layers, and n is selected from 1, 2, or 3.
[0007] In an embodiment of the present invention, the transition metal nanoparticles include at least one of Fe nanoparticles, Cu nanoparticles, Co nanoparticles, and Ni nanoparticles.
[0008] Preferably, the particle size of the transition metal nanoparticles is 1 to 100 nm.
[0009] Preferably, the particle size of the Se particles is 1 to 100 nm.
[0010] Preferably, the molar ratio of MXene material to transition metal nanoparticles is 1:1 to 1:5.
[0011] Preferably, the mass ratio of Se particles to host material is 1:1 to 4:1.
[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps: S1, uniformly mixing the MAX phase material, the transition metal chloride, and the molten salt medium to obtain a first mixture; performing a molten salt etching treatment on the first mixture in an inert gas atmosphere to remove water-soluble salts, and then drying to obtain a host material including MXene materials and transition metal nanoparticles; S2, uniformly mixing the host material and the Se powder to obtain a second mixture; sintering and grinding the second mixture in an inert gas atmosphere to obtain a positive electrode material.
[0013] In an embodiment of the present invention, the chemical formula of the MAX phase material is M n+1 AX n , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, A is at least one of Al, Ga, Zn, Si, P, S, Ge, As, Cd, In, Sn, Tl, and Pb, X is C and / or N elements, and n is the number of layers, which is selected from 1, 2, or 3.
[0014] In an embodiment of the present invention, the transition metal chloride includes at least one of FeCl2, CuCl2, CoCl2, and NiCl2.
[0015] In an embodiment of the present invention, the molten salt medium includes alkali metal chloride.
[0016] Preferably, the molar ratio of the MAX phase material, the transition metal chloride, and the molten salt medium is 1:(1-5):(4-10).
[0017] Preferably, in step S1, the heating rate of the molten salt etching process is 1-10 °C min -1The holding temperature of the molten salt etching treatment is 700-800 °C, and the holding time of the molten salt etching treatment is 10-24 h.
[0018] Preferably, in step S2, the firing temperature is 200-300°C, and the holding time of the firing is 2-4 hours.
[0019] In a third aspect, the present invention provides a positive electrode sheet, which includes the positive electrode material mentioned above, and / or the positive electrode material prepared by the above preparation method.
[0020] In a fourth aspect, the present invention provides a sodium-selenium battery, which includes the above-mentioned positive electrode sheet.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. The cathode material of the present invention includes an accordion-shaped MXene host material modified by transition metal nanoparticles and Se particles. The host material, as a two-dimensional confined-catalytic structure, can largely inhibit the volume expansion effect of selenium and limit the shuttling effect of polyselenides; the transition metal nanoparticles modified on the surface of the host material effectively promote the reaction kinetics between the sodium electrode and the selenium electrode, enhance the charge transfer of the selenium cathode, and achieve high power density and high energy density of the sodium-selenium battery. It can be seen that the host material starts from three aspects: limiting the volume expansion of selenium, inhibiting the shuttling effect of polyselenides, and accelerating the reaction speed of the selenium electrode and the sodium electrode, and jointly achieves the high power density and high energy density of the sodium-selenium battery.
[0022] First, the layered structure of the host material provides nanoscale space to confine Se; second, there is strong chemical adsorption between the surface-O end groups of MXene materials and Se, which hinders the shuttling effect; finally, the transition metal (such as Fe) nanoparticles modified on the surface of MXene materials act as active centers to promote the charge transfer of sodium polyselenide, which can effectively promote the conversion of long-chain (Na2Se8, Na2Se6, Na2Se4, Na2Se2) to short-chain (Na2Se) polyselenides and accelerate the electrochemical reaction kinetics. Specifically, the anchored transition metal nanoparticles can catalyze the conversion of liquid phase Na2Se n The host material not only hinders the dissolution and shuttling of polyselenides through confinement effects such as spatial confinement and chemical adsorption, but also plays a catalytic role in promoting the conversion of long-chain polyselenides to short-chain polyselenides.
[0023] In addition, since MXene materials and transition metals have excellent electrical conductivity and are excellent conductors of electrons, the confined-catalytic structure also helps to achieve high-rate performance of the battery.
[0024] 2. The cathode material of the present invention, such as Se@MXene / Fe cathode material, has a large Se loading of 74.9 wt %. -1 575.0 mAh g -1 Even at 50 A g -1 Even at high charging rates, it can still maintain 500 mAh g -1 The high specific capacity shows an ultra-high capacity retention rate of 88.5%.
[0025] 3. The cathode material of the present invention has an excellent long-term cycling capability at 10 A g -1 After 5000 cycles, it can still maintain 494.6 mAh g -1 The high specific capacity of the material highlights its structural stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 SEM image of MXene / Fe host material.
[0027] Figure 2 This is the SEM image of Se@MXene / Fe positive electrode material.
[0028] Figure 3 XRD pattern of the positive electrode material.
[0029] Figure 4 is the GCD curve of the electrode.
[0030] Figure 5 This is the rate performance diagram of the electrode.
[0031] Figure 6 Example 1 (Se@MXene / Fe), Comparative Example 1 (Se), Comparative Example 2 (Se@MXene) at 0.2 A g -1 The cycle stability of the battery system was tested by charging and discharging for 300 cycles at a current density of .
[0032] Figure 7 Example 1 (Se@MXene / Fe), Comparative Example 1 (Se), Comparative Example 2 (Se@MXene) at 10 A g -1 The cycle stability of the battery system was tested by charging and discharging for 5000 cycles at a current density of . DETAILED DESCRIPTION
[0033] The present invention discloses a positive electrode material and a preparation method thereof and a sodium-selenium battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the above. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0034] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0035] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0036] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0040] Specifically, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a positive electrode material, the positive electrode material comprising a host material and Se particles; The host material includes a MXene material and transition metal nanoparticles. The MXene material has an accordion-like layered structure, and the transition metal nanoparticles are modified on the surface of the MXene material. Se particles are loaded on the surface of MXene materials and between their layered structures.
[0041] The cathode material of the present invention includes an accordion-shaped MXene host material modified by transition metal nanoparticles and Se particles. The host material, as a two-dimensional confinement-catalysis structure, can largely suppress the volume expansion effect of selenium and limit the shuttling effect of polyselenides; the transition metal nanoparticles modified on the surface of the host material effectively promote the reaction kinetics between the sodium electrode and the selenium electrode, enhance the charge transfer of the selenium cathode, and achieve high power density and high energy density of the sodium-selenium battery. It can be seen that the host material starts from three aspects: limiting the volume expansion of selenium, suppressing the shuttling effect of polyselenides, and accelerating the reaction speed of the selenium electrode and the sodium electrode, and jointly achieves the high power density and high energy density of the sodium-selenium battery. In addition, since both MXene materials and transition metals have excellent electrical conductivity and are excellent conductors of electrons, the confinement-catalysis structure also helps to exert the high rate performance of the battery. At the same time, the cathode material of the present invention has ultra-high capacity retention and excellent long-term cycle capacity.
[0042] In an embodiment of the present invention, the chemical formula of the MXene material is M n+1 X n T x , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, X is C and / or N, T x is at least one of the surface functional groups -O, -Cl, -OH, -F, n is the number of layers, and n is selected from 1, 2 or 3. The layered structure of MXene materials provides nanoscale space to confine Se and inhibit the volume expansion effect of selenium; secondly, there is a strong chemical adsorption between the surface -O end group of MXene materials and Se, which will hinder the shuttle effect; in addition, because MXene materials have excellent electrical conductivity and are excellent conductors of electrons, they are helpful for the high rate performance of batteries.
[0043] In a specific embodiment of the present invention, the MXene material is selected from Ti3C2T x 、Ti2CT x 、V2CT x 、Ti2NT x 、(Mo2Ti)C2T x 、Mo 1.33 Y0.66 CT x 、(Mo2Sc)C2T x 、(Ti,V,Zr,Nb,Ta)2CT x 、(Ta,Ti)3C2T x , W 1.33 CT x 、Zr3C2T x 、Hf2CTx、Hf2NT x One of them. For example, Ti3C2Cl2, Ti3C2O2, etc.
[0044] In a specific embodiment of the present invention, T x are the surface functional groups -O and -Cl.
[0045] In an embodiment of the present invention, the transition metal nanoparticles include at least one of Fe nanoparticles, Cu nanoparticles, Co nanoparticles, and Ni nanoparticles. The transition metal nanoparticles modified on the surface of the MXene material serve as active centers to promote the charge transfer of sodium polyselenide, and can effectively promote the conversion of long-chain (Na2Se8, Na2Se6, Na2Se4, Na2Se2) to short-chain (Na2Se) polyselenides, effectively promoting the reaction kinetics between the sodium electrode and the selenium electrode, enhancing the charge transfer of the selenium positive electrode, and achieving high power density and high energy density of the sodium selenium battery. In addition, since transition metals have excellent electrical conductivity and are excellent conductors of electrons, they contribute to the high rate performance of the battery.
[0046] Preferably, the particle size of the transition metal nanoparticles is 1 to 100 nm. Exemplarily, the particle size of the transition metal nanoparticles is any value among 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value within the range of any two of the above values. Within this particle size range, it is helpful to modify the transition metal nanoparticles on the surface of the MXene material.
[0047] Preferably, the particle size of the Se particles is 1 to 100 nm. Exemplarily, the particle size of the Se particles is any value among 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value within the range of any two of the above values. The Se particles are nanometer-sized and can be limited by the nanometer-sized space of the layered structure of the host material, thereby achieving the purpose of suppressing the volume expansion effect of selenium.
[0048] Preferably, the molar ratio of MXene material to transition metal nanoparticles is 1:1 to 1:5. Exemplarily, the molar ratio of MXene material to transition metal nanoparticles is any value among 1:1, 1:2, 1:3, 1:4, 1:5 or any value within the range of any two of the above values. When the proportion of transition metal nanoparticles is too small, the amount of transition metal chloride (such as FeCl2) in the positive electrode material preparation method is small, and the precursor MAX (M n+1 AX n ) is completely etched, and the resulting host material is defective, which limits the subsequent restriction on Se. When the proportion of transition metal (such as Fe) nanoparticles is too large, the introduced transition metal is excessive, and it is necessary to add a transition metal removal step in the subsequent process, which increases the difficulty of operation. In addition, when the introduced transition metal content is too high, the content of Se in the battery active material is reduced accordingly, causing the battery capacity to decay, which is not conducive to the full play of the performance of the active material.
[0049] Preferably, the mass ratio of Se particles to host materials is 1:1 to 4:1. Exemplarily, the mass ratio of Se particles to host materials is any value among 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1 or any value within the range of any two of the above values. As positive electrode active materials, Se particles participate in electrochemical reactions to store and release energy. When the proportion of Se particles is too small, the content of active material Se is low and its performance cannot be fully exerted; when the proportion of Se particles is too large, the content of Se far exceeds the range that can be limited by the host material, which reduces the confinement effect of the host material and leads to the attenuation of battery performance.
[0050] In a second aspect, the present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps: S1, uniformly mixing the MAX phase material, the transition metal chloride, and the molten salt medium to obtain a first mixture; performing a molten salt etching treatment on the first mixture in an inert gas atmosphere to remove water-soluble salts, and then drying to obtain a host material including MXene materials and transition metal nanoparticles; S2, uniformly mixing the host material and the Se powder to obtain a second mixture; sintering and grinding the second mixture in an inert gas atmosphere to obtain a positive electrode material.
[0051] In an embodiment of the present invention, the chemical formula of the MAX phase material is M n+1 AX n, wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, A is at least one of Al, Ga, Zn, Si, P, S, Ge, As, Cd, In, Sn, Tl, and Pb, X is C and / or N elements, and n is the number of layers, which is selected from 1, 2, or 3.
[0052] In an embodiment of the present invention, exemplarily, the MAX phase material includes at least one of Ti3AlC2, Ti2AlC, V2AlC, Cr2AlC, Ti3AlCN, Nb2GaC, and Cr2ZnC.
[0053] In an embodiment of the present invention, the transition metal chloride includes at least one of FeCl2, CuCl2, CoCl2, and NiCl2. As a Lewis acid, the transition metal chloride undergoes a redox reaction with the A element in the MAX main structure through cations in a high-temperature molten salt environment, thereby achieving selective etching of the A layer atoms in the MAX phase. At the same time, the chloride ions in the transition metal chloride can coordinate with the metal atoms on the surface of the MXene to form surface functional groups of the MXene. The use of transition metal chlorides not only provides an anhydrous and oxygen-free etching environment, but also helps to avoid the chemical safety hazards and waste liquid treatment problems that may be caused by the use of traditional hydrofluoric acid etching methods.
[0054] In the embodiment of the present invention, etching by transition metal chloride can achieve T x are surface functional groups -O and -Cl. If we want to achieve T x For the surface functional groups -OH and -F, other conventional etching methods in the art need to be used.
[0055] In an embodiment of the present invention, the molten salt medium includes alkali metal chloride. In an embodiment of the present invention, illustratively, the molten salt medium includes at least two of NaCl, KCl, and LiCl.
[0056] In the embodiment of the present invention, the main functions of the molten salt medium include: 1) Forming a uniform etching environment: The anions and cations in the molten salt medium can provide a uniform etching environment, which helps to obtain a uniform MXene layered structure; 2) Provide a high electrochemical window: The molten salt medium has a wide electrochemical window, which is conducive to redox reactions and promotes the etching of element A in the MAX phase; 3) Promote the replacement of element A: Na + and K +The cations undergo a replacement reaction with the A element in the MAX phase, so that the A element is separated from the MAX structure to form MXene; however, the Na / K ions do not remain in the MAX phase structure, but are removed by washing after the reaction. For example, washing with water can achieve the removal of Na-containing ions in step S1. + and K + The purpose of water-soluble salts (NaCl and KCl).
[0057] Preferably, the molar ratio of the MAX phase material, the transition metal chloride, and the molten salt medium is 1:(1-5):(4-10). Exemplarily, the molar ratio of the MAX phase material, the transition metal chloride, and the molten salt medium is any value among 1:1:10, 1:5:10, 1:1:4, 1:5:4, 1:3:6, or any value within the range of any two of the above values.
[0058] Preferably, in step S1, the heating rate of the molten salt etching process is 1-10 °C min -1 The holding temperature of the molten salt etching treatment is 700-800 °C, and the holding time of the molten salt etching treatment is 10-24 h. Exemplarily, the heating rate of the molten salt etching treatment is 1 °C min -1 、2℃min -1 、4℃ min -1 、6℃ min -1 、8℃ min -1 、10℃min -1 The holding temperature of the molten salt etching treatment is any value in 700 ℃, 720 ℃, 740 ℃, 760 ℃, 780 ℃, 800 ℃ or any value in the range composed of any two of the above values; the holding time of the molten salt etching treatment is any value in 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h or any value in the range composed of any two of the above values.
[0059] Preferably, in step S1, the drying temperature is 60-100° C., and the drying time is 4-8 h.
[0060] Taking the MAX phase material as Ti3AlC2 and the transition metal chloride as FeCl2 as an example, in the molten salt etching process, the reaction equation for the reaction between Ti3AlC2 and FeCl2 to synthesize the host material is as follows: Ti3AlC2+ 1.5FeCl2→ Ti3C2+ AlCl3↑ + 1.5Fe Ti3C2+ FeCl2→ Ti3C2Cl2+ Fe Ti3C2+ 2H2O → Ti3C2(OH)2+ H2 Ti3C2(OH)2→ Ti3C2O2+ H2 In the synthesis of host materials, MAX is used as the main structure, and transition metal chloride (such as FeCl2) is used as Lewis acid. The cations in the high-temperature molten salt environment undergo redox reactions with the A element (such as Al) to achieve selective etching of the A layer atoms in the MAX phase. At the same time, the chloride ions in the transition metal chloride can coordinate with the metal atoms on the surface of the MXene to form the surface functional group -Cl end group of the MXene. The use of transition metal chloride not only provides an anhydrous and oxygen-free etching environment, but also helps to avoid the chemical safety hazards and waste liquid treatment problems that may be caused by the use of traditional hydrofluoric acid etching methods.
[0061] Preferably, in step S2, the temperature of the firing treatment is 200-300°C, and the holding time of the firing treatment is 2-4 hours. Exemplarily, the temperature of the firing treatment is any value in 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, or any value in the range of any two of the above values, and the holding time of the firing treatment is any value in 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, or any value in the range of any two of the above values.
[0062] Preferably, in step S1 or S2, the mixing is performed uniformly by grinding, and the grinding time is 5 to 15 minutes.
[0063] In a third aspect, the present invention provides a positive electrode sheet, which includes the positive electrode material mentioned above, and / or the positive electrode material prepared by the above preparation method.
[0064] In an embodiment of the present invention, the positive electrode sheet further includes a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, and those skilled in the art can select them according to actual needs, as long as the purpose of the present application can be achieved. The amounts of the conductive agent and the binder are conventional amounts in the art, and the present invention will not be repeated here.
[0065] In a fourth aspect, the present invention provides a sodium-selenium battery, which includes the above-mentioned positive electrode sheet.
[0066] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0067] The present application has no particular restrictions on the negative electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0068] The present invention uses a Cu-Kα radiation source (λ=1.5406 Å) to record X-ray diffraction (XRD) patterns on a multifunctional horizontal X-ray diffractometer (Smartlab9kw, Japan).
[0069] The present invention characterizes the material microstructure by SEM (ZEISS Gemini 300) at an accelerating voltage of 30 kV.
[0070] The instrument used in the electrochemical test of the present invention is a Xinwei battery testing system.
[0071] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0072] The present invention will be further described below in conjunction with embodiments: Embodiment 1: 1. Synthesis of Se@MXene / Fe cathode materials: (1) Ti3AlC2MAX phase, FeCl2·4H2O, NaCl, and KCl were mixed and ground in a molar ratio of 1:3:2:2 for 10 min. Subsequently, the mixture was annealed at 700 °C in an argon atmosphere for 10 h with a heating rate of 5 °C min -1 After cooling to room temperature, the mixture was washed with deionized water to remove water-soluble salts, vacuum filtered to obtain a filter cake, and then vacuum dried at 80 °C for 6 h. The product obtained after cooling to room temperature was named MXene / Fe host material. Its SEM image is shown in Figure 1 shown. Figure 1 The SEM revealed the morphology of the MXene / Fe host material with nanoscale particles, perfectly preserved the layered structure, and Fe nanoparticles were uniformly modified on the MXene surface, indicating that the MXene / Fe host material has the potential to serve as a spatial confinement and catalytic structure for Se.
[0073] (2) Mix MXene / Fe and Se in a mass ratio of 1:3, and then grind for 10 min to mix the two evenly. The powder obtained after mixing evenly is placed in a tube furnace in an argon atmosphere and kept at 260 °C for 3 h. After cooling to room temperature, the fired product is ground into fine particles. This product is the Se@MXene / Fe positive electrode material, and its SEM image is shown in Figure 2 shown. Figure 2 SEM shows that the surface of MXene / Fe is uniformly covered with a layer of Se.
[0074] 2. Preparation of positive electrode: The active material (Se@MXene / Fe cathode material) was mixed with the conductive agent (Super P) and the binder (PVDF) in a mass ratio of 8:1:1, ground evenly, and NMP was used as the solvent. The mixed slurry was then placed on a magnetic stirrer and stirred for 10 h. After stirring evenly, the slurry was applied to the copper foil, which was vacuum dried at 60 °C for 10 h, and then cut into 10 mm diameter pole pieces with a slicer (the mass loading of the active material was about 1 mg cm -2 ), for subsequent battery assembly.
[0075] 3. Battery assembly: Assembly of 2032 button cells: 1 M sodium hexafluorophosphate (NaPF6) dissolved in ethylene glycol dimethyl ether (DME) was used as the electrolyte, and a glass fiber separator was used as the separator. The cells were assembled in an argon glove box with oxygen and water contents below 1 ppm. The specific sequence was as follows: first place the negative electrode of the battery shell, then the positive electrode sheet, then the three layers of glass fiber separator, add 230 μL of electrolyte, then place the sodium sheet as the counter electrode, place the gasket and the spring sheet, then place the positive electrode of the battery shell, and finally apply a pressure of 10 Mpa to the assembled battery to compress and seal the battery.
[0076] Embodiment 2: The difference between this embodiment and embodiment 1 is that: When synthesizing the Se@MXene / Fe cathode material, MXene / Fe and Se were mixed in a mass ratio of 1:2.
[0077] Embodiment 3: The difference between this embodiment and embodiment 1 is that: When synthesizing the Se@MXene / Fe cathode material, MXene / Fe and Se were mixed in a mass ratio of 1:4.
[0078] Embodiment 4: The difference between this embodiment and embodiment 1 is that: In the synthesis of Se@MXene / Fe cathode material, Ti3AlC2MAX phase, FeCl2·4H2O, NaCl and KCl were mixed and ground in a molar ratio of 1:1:2:2 for 10 min.
[0079] Embodiment 5: The difference between this embodiment and embodiment 1 is that: In the synthesis of Se@MXene / Fe cathode material, Ti3AlC2MAX phase, FeCl2·4H2O, NaCl and KCl were mixed and ground in a molar ratio of 1:5:2:2 for 10 min.
[0080] Embodiment 6: The difference between this embodiment and embodiment 1 is that: In the synthesis of Se@MXene / Cu cathode material, Ti2AlCMAX phase, CuCl2, NaCl and KCl were mixed and ground in a molar ratio of 1:3:2:2 for 10 min, and MXene / Cu and Se were mixed in a mass ratio of 1:3.
[0081] Comparative Example 1: The positive electrode material of this comparative example is Se, and the specific preparation method of the sodium selenium battery is as follows: 1. Treatment of Se Grind the Se powder for 10 min to make the selenium powder particles fine and uniform. Place the ground selenium powder in a tube furnace in an argon atmosphere at 260 °C for 3 h. After cooling to room temperature, fully grind the fired product into fine particles, which is Se.
[0082] 2. Preparation of positive electrode: The active material (Se) was mixed with the conductive agent (Super P) and the binder (PVDF) in a mass ratio of 8:1:1, and after grinding, NMP was used as the solvent. The mixed slurry was then placed on a magnetic stirrer and stirred for 10 h. After stirring evenly, the slurry was applied to the copper foil, which was vacuum dried at 60 °C for 10 h, and then cut into 10 mm diameter pole pieces with a slicer (the mass loading of the active material is about 1 mg cm -2 ), for subsequent battery assembly.
[0083] 3. The battery assembly process is the same as that of Example 1.
[0084] Comparative Example 2: The positive electrode material of this comparative example is Se@MXene, and the specific preparation method of the sodium selenium battery is as follows: 1. Synthesis of Se@MXene cathode materials: Synthesis of accordion-shaped Ti3C2T by etching Al atomic layers of MAX phase x MXene. 1 g of Ti3AlC2 powder was slowly added to 20 mL of HF and stirred at room temperature for 24 h for etching. The etched product was then centrifuged and washed with ultrapure water until neutral, filtered with a vacuum pump, and vacuum dried at 60 °C for 3 h. After cooling to room temperature, it was evenly ground to obtain an accordion-shaped MXene.
[0085] Se@MXene is synthesized from MXene and Se powder. The accordion-shaped MXene and Se are mixed in a mass ratio of 1:3, and then ground for 10 min to make the two evenly mixed. The powder obtained after uniform mixing is placed in a tube furnace in an argon atmosphere at 260 ° C for 3 h. After cooling to room temperature, the fired product is fully ground into fine particles. This product is Se@MXene.
[0086] 2. Preparation of positive electrode: The active material (Se@MXene) was mixed with the conductive agent (Super P) and the binder (PVDF) in a mass ratio of 8:1:1, and after grinding, NMP was used as the solvent. The mixed slurry was then placed on a magnetic stirrer and stirred for 10 h. After stirring evenly, the slurry was applied to the copper foil, which was vacuum dried at 60 °C for 10 h, and then cut into 10 mm diameter pole pieces with a slicer (the mass loading of the active material was about 1 mg cm -2 ), for subsequent battery assembly.
[0087] 3. The battery assembly process is the same as that of Example 1.
[0088] XRD test of positive electrode materials XRD tests were performed on the positive electrode materials in Example 1 and Comparative Examples 1-2. Se in Comparative Example 1, Ti3C2T in Comparative Example 2 x The XRD spectra of MXene and Se@MXene, as well as MXene / Fe and Se@MXene / Fe of Example 1 are as follows: Figure 3 As shown in Figure 2, it can be observed that the Al layer is successfully etched in MXene. During the etching process, Fe 2+ The Fe@MXene / Fe hosts were reduced to metallic Fe atoms and then partially aggregated into particles and / or clusters. Therefore, a significant Fe metal diffraction signal was observed in the MXene / Fe host. In addition, Se was also observed in Se@MXene and Se@MXene / Fe samples, indicating that Se was successfully loaded onto the MXene and MXene / Fe hosts. Surprisingly, the XRD diffraction peaks of MXene and Fe almost disappeared due to the high amount of Se loaded on the host surface.
[0089] Battery performance test 1. Test methods (1) Galvanostatic Charge-Discharge (GCD) 0.1~2.5 V vs. Na + / Na in the voltage range of 0.2, 0.5, 1, 2, 5, 10, 20, 30, 50 A g-1 GCD curve of the battery system tested at a current density of .
[0090] (2) Rate performance test 0.1~2.5 V vs. Na + / Na in the voltage range of 0.2, 0.5, 1, 2, 5, 10, 20, 30, 50 A g -1 Run 10 times at each current density to test the rate performance of the battery system.
[0091] (3) Stability test 0.1~2.5 V vs. Na + / Na in the voltage range of 0.2, 10 A g -1 The cycle stability of the battery system was tested by charging and discharging for 300 and 5000 cycles at a current density of .
[0092] 2. Test results Table 1 Rate performance test results Table 2 Stability test results Figure 4 The Se@MXene / Fe electrode of Example 1 was -1 to 50 A g -1 The GCD curve in the range of 200 A g / cm2 and the Coulomb efficiency is as high as 100%. -1 The voltage platform can still be maintained at a high rate, indicating that the Se@MXene / Fe electrode has ultrafast charge storage performance.
[0093] Table 1 and Figure 5 The rate performance diagram shows that the Se@MXene / Fe electrode of Example 1 can -1 At a current density of 500 mAh g -1 Specific capacity. In Examples 2, 3, 4, and 5, the Se@MXene / Fe electrode was -1 The specific capacities at current densities of 372.6, 485.3, 449.4, and 439.1 mAh g -1 The Se@MXene / Cu electrode in Example 6 was -1 The specific capacity at a current density of 531.7 mAh g -1. Comprehensive comparison of Examples 1, 2, 3, 4, 5, and 6 shows that the Se@MXene / Fe electrode in Example 1 exhibits better performance at different current densities, and is the best group. The performance of the six examples is in the following order from best to worst: Example 1> Example 6> Example 3> Example 4> Example 5> Example 2. Because the content of selenium is low and the active material is less, the rate and cycle specific capacity of Example 2 are poor; because the content of selenium is too high, the MXene / Fe host structure cannot effectively inhibit the volume expansion and the shuttle effect of polyselenide for excessive selenium, so the performance of Example 3 is reduced; because the content of Fe is low in Example 4, the catalytic effect of Fe cannot be fully exerted, so the performance of Example 4 is reduced; because the content of Fe is too high in Example 5, the proportion of MXene in the same mass of MXene / Fe is small, so that the MXene / Fe host structure has a weakened inhibitory effect on the volume expansion of selenium and the shuttle effect of polyselenide, resulting in a decrease in the performance of Example 5; in Example 6, the main material and surface nanoparticles of the host structure are changed, and the performance is slightly reduced.
[0094] At the same time, due to the severe shuttle effect of polyselenides and the low activity of Se, the Se in Comparative Example 1 and the Se@MXene electrodes in Comparative Example 2 were -1 The capacities at high current densities are only 217.5 and 367.0 mAh g -1 It is noteworthy that even when the applied current density is reversed to 0.2 A g -1 When , the Se@MXene / Fe electrode of Example 1 can still obtain 575.0 mAh g -1 This shows that the Se@MXene / Fe electrode of Example 1 has a high stable discharge specific capacity even at a high -1 The electrode structure can still be guaranteed to be stable and not destroyed under the current density, and the electrode reaction has good reversibility.
[0095] Table 2 Figure 6 and Figure 7 The stability test results show that the cyclic stability of Se@MXene / Fe in Example 1, Se@MXene in Comparative Example 2, and Se electrode in Comparative Example 1 is 0.2 A g after activation. -1 and 10 A g -1 Even after 300 cycles, the Se@MXene / Fe, Se@MXene, and Se electrodes showed extremely stable specific capacities of 563, 470, and 256 mAh g, respectively. -1, indicating their structural stability at low current densities. Impressively, the Se@MXene / Fe electrodes -1 After 5000 cycles, the electrode can still maintain a capacity of 97.4%, with a capacity decay rate of only 0.0006% per cycle, and has a nearly perfect coulombic efficiency during the entire cycle. However, the cycle performance of Examples 2, 3, 4, 5, and 6 has decreased to varying degrees compared with that of Example 1.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes a host material and Se particles; The host material includes a MXene material and transition metal nanoparticles, the MXene material has an accordion-shaped layered structure, and the transition metal nanoparticles are modified on the surface of the MXene material; The Se particles are loaded on the surface of the MXene material and between its layered structures.
2. The positive electrode material according to claim 1, characterized in that The chemical formula of the MXene material is M n+1 X n T x , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, and Hf, X is C and / or N, T x is at least one of the surface functional groups -O, -Cl, -OH, -F, n is the number of layers, and n is selected from 1, 2 or 3; And / or, the transition metal nanoparticles include at least one of Fe nanoparticles, Cu nanoparticles, Co nanoparticles, and Ni nanoparticles; and / or, the particle size of the transition metal nanoparticles is 1 to 100 nm; And / or, the particle size of the Se particles is 1 to 100 nm.
3. The positive electrode material according to claim 1, characterized in that The molar ratio of the MXene material to the transition metal nanoparticles is 1:1 to 1:5; And / or, the mass ratio of the Se particles to the host material is 1:1 to 4:
1.
4. A method for preparing a positive electrode material, characterized in that: The steps include: S1, uniformly mixing a MAX phase material, a transition metal chloride, and a molten salt medium to obtain a first mixture; subjecting the first mixture to a molten salt etching treatment in an inert gas atmosphere to remove water-soluble salts, and then drying to obtain a host material including a MXene material and transition metal nanoparticles; S2, mixing the host material and Se powder uniformly to obtain a second mixture; sintering and grinding the second mixture in an inert gas atmosphere to obtain a positive electrode material.
5. The preparation method according to claim 4, characterized in that: The chemical formula of the MAX phase material is M n+1 AX n , wherein M is at least one of the transition metal elements Ti, V, Nb, Cr, Sc, Mo, Y, Zr, Ta, W, Hf, A is at least one of Al, Ga, Zn, Si, P, S, Ge, As, Cd, In, Sn, Tl, Pb, X is C and / or N element, n is the number of layers, and n is selected from 1, 2 or 3; And / or, the transition metal chloride includes at least one of FeCl2, CuCl2, CoCl2, and NiCl2; And / or, the molten salt medium includes alkali metal chloride.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the MAX phase material, the transition metal chloride and the molten salt medium is 1:(1-5):(4-10).
7. The preparation method according to claim 4, characterized in that: In step S1, the heating rate of the molten salt etching process is 1-10 °C min -1 The holding temperature of the molten salt etching treatment is 700-800°C, and the holding time of the molten salt etching treatment is 10-24 h.
8. The preparation method according to claim 4, characterized in that: In the step S2, the temperature of the sintering treatment is 200-300°C, and the holding time of the sintering treatment is 2-4 hours.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 3, and / or the positive electrode material prepared by the preparation method according to any one of claims 4 to 8.
10. A sodium-selenium battery, characterized in that: The sodium-selenium battery comprises the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Preparation method of lithium-sulfur battery positive electrode material with high conductivity and strong adsorption
CN113488638A
Double-carrier conduction all-solid-state battery electrode material and preparation method thereof
CN114864901A
Se@MXene composite materials and their preparation methods and all-solid-state lithium batteries
CN114933286A
Preparation method of Ti2CTx particle loaded metal Co / Ni composite nanomaterial
CN117161375A
Diaphragm, preparation method thereof and lithium battery
CN119108759A